Asisten Virtual sebagai Pusat Layanan Informasi pada Perguruan Tinggi di Indonesia – A Systematic Literature Review - Amalia Anjani Arifiyanti; Reisa Permatasari; Abdul Rezha Efrat Najaf (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
The ease of providing information services is one aspect of public services that must be fulfilled by higher education institutions. However, this requires quite a bit of resources to handle the large number of requests for information availability. Virtual assistants can be the answer to providing information easily and quickly. Virtual assistants have been widely used by various institutions to provide information services that are fast and can be accessed at any time. This study was conducted to study what types of methods and approaches can be applied to the development of virtual assistants in Indonesia. This study uses the Systematic Literature Review approach. A review was carried out on 13 selected articles that discussed the application of virtual assistants in higher education in Indonesia. As a result, virtual assistants can be applied in various forms with various development method approaches. In addition, it was also found that all academic service information provision and academic operational support owned by higher education institutions can be assisted by virtual assistants